Kilka uwag o omylności i meta logu. Na marginesie książki Andrzej Nowakowskiego Uzasadnienie epistemiczne - Paprzycka, Katarzyna (Filozofia Nauki, 2014)
The paper is a critical notice of Andrzej Nowakowski’s book on epistemic justification (Andrzej Nowakowski, Uzasadnienie epistemiczne, Wydawnictwo UMCS, Lublin 2011). I examine the author’s discussion of the third condition on knowledge and expose multiple errors. The main problem with Nowakowski’s proposal is that it is seriously underdeveloped. Moreover, under the most natural interpretation, it suf-fers from many of the same problems as some of the accounts Nowakowski criticizes.